THE IMPACT OF SIDE JOBS ON TEACHING PROFESSIONALISM AMONG TEACHERS IN ISLAMIC BOARDING SCHOOLS AND REGULAR SCHOOLS - Wahyuddin, Wahyuddin (Lembaga Penelitian Mahasiswa Penalaran UNM, 2025)
This study investigates the impact of side jobs (moonlighting) on teaching professionalism among teachers in Islamic boarding schools and regular schools using quantitative methodologies. Conducted in Majene and Polman Districts, the study involved 109 randomly selected teachers who completed a side-job survey and a teacher professionalism questionnaire. These instruments provided data on side job participation, professionalism, and demographic variables such as gender, school type, and side job status. Descriptive statistical analysis was used to summarize key trends, measure central tendencies, and assess variability within the dataset. Additionally, Analysis of Variance (ANOVA) was employed to examine differences in professionalism scores among groups, determining whether side job engagement or school type had a statistically significant effect. The results showed no significant differences in professionalism scores between teachers with and without side jobs, regardless of school type. The findings suggest that side job engagement does not negatively affect teachers' professional practices or teaching commitment. Despite added responsibilities, teachers actively mitigate any potential negative impacts on their duties, maintaining their professionalism across diverse educational environments.